Gonial Angle as a Tool in Determination of Gender Using Orthopantomogram in South Indian Population - Panigrahi, Chandan; Arthanari, Abirami (Journal of Neonatal Surgery, 2024)
Introduction- The determination of sex from human remains has a crucial role in forensic anthropology. It has been known that the mandible has several useful traits for sex determination. The gonial angle, also referred to as the mandibular angle or angle of the mandible, is formed at the confluence of the posterior border of the ramus and the lower border of the mandible. This angle, subject to sexual dimorphism, manifests distinct variations between males and females. Typically, males exhibit a wider and more obtuse gonial angle, while females display a narrower and more acute angle. This inherent anatomical difference lays the foundation for gender determination when scrutinizing OPGs. Materials and Methods- 50 OPGs (25 males and 25 females) were analyzed, the value of the gonial angle was measured and then it was subjected to statistical analysis using SPSS software to determine gender. Results- The results were insignificant as the p value was p> 0.05. Discussion- Various parameters of the mandible have been successfully used to estimate sex of individuals. Conclusion- The gonial angle of the mandible is not a reliable marker of sex estimation..